2014
DOI: 10.1002/etc.2552
|View full text |Cite
|
Sign up to set email alerts
|

Implications of interacting microscale habitat heterogeneity and disturbance events on Folsomia candida (Collembola) population dynamics: A modeling approach

Abstract: The authors implemented a fractal algorithm in a spatially explicit individual-based model to generate landscapes with different microscale patterns of habitat fragmentation and disturbance events and studied their effects on population dynamics of the collembolan Folsomia candida. Among human activities that may cause habitat destruction, the present study focused on agricultural practices. Soil organisms living in a cultivated field are subjected to habitat loss and fragmentation as well as disturbance event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…; Salmon et al . ), in estimating sublethal effects of chemical agents in ecotoxicology (van Gestel ), in allometric studies (Mulder ) and in population growth modelling (Meli, Palmqvist & Forbes ). Techniques already exist to automatize these time‐consuming measurements in the laboratory (Mallard, Le Bourlot & Tully ; Bánszegi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Salmon et al . ), in estimating sublethal effects of chemical agents in ecotoxicology (van Gestel ), in allometric studies (Mulder ) and in population growth modelling (Meli, Palmqvist & Forbes ). Techniques already exist to automatize these time‐consuming measurements in the laboratory (Mallard, Le Bourlot & Tully ; Bánszegi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Body size of microarthropods and other invertebrates in soils is commonly measured in trait analyses for community assessment and ecological indicator studies (Bokhorst et al 2012;Salmon et al 2014), in estimating sublethal effects of chemical agents in ecotoxicology ( van Gestel 2012), in allometric studies (Mulder 2006) and in population growth modelling (Meli, Palmqvist & Forbes 2014). Techniques already exist to automatize these time-consuming measurements in the laboratory (Mallard, Le Bourlot & Tully 2013;B anszegi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of the favourable habitats within a landscape has been shown to be important for maintaining the persistence of populations (Dytham 1995, Meli et al 2014. Surprisingly, we found that increasing the number of patches affected by drought at different speeds only negatively affect the maximum rate of population decline, rather than the timing of extinctions, which may suggest a tipping point for environmental conditions as a result of increased drought habitats destabilising populations.…”
Section: Discussionmentioning
confidence: 60%
“…was low (less than 5 collembola per sample), and varied little throughout the cultivation (Figure 4B). causing their death due to the mechanical impact of this practice as well as it affects the reduction of food resources for these arthropods (Meli et al, 2014;Coulibaly et al al., 2017;Müller et al, 2022). Straw on the soil favorably affected the abundance of Collembola on the soil of bean crops, possibly because it serves as a shelter and food and provides an adequate microhabitat for these arthropods (Andrén & Schnürer, 1985;Dittmer & Schrader, 2000;Mint, 2012).…”
Section: Resultsmentioning
confidence: 99%